IMPROVING LEGAL ARGUMENT CRITICALLY IN THE LITIGATION MECHANISM IN INDONESIA (AN EMPIRICAL STUDY OF ENVIRONMENTAL VERDICTS) - Edy Lisdiyono (Faculty of Law, Sriwijaya University, Indonesia, 2017)
Legal argument is a debate or argument in explaining the issues between two or more people performed in court. Legal argument is one way to perform law finding with the purpose to avoid legal vacuum when the judge makes a legal reasoning in a verdict. In making a legal argument, it is at least performed by legal reasoning, logic, facts. However, some judges, in making a decision, did not use the legal arguments by legal reasoning and facts so that it resulted in debates and arguments. It is interesting to study on how to build legal argument in the litigation mechanism in Indonesia. Some verdicts in Indonesia have been the debate among the public through social media, by both academic and non-academic communities, because they were not based on the legal facts revealed at the trials and not in favor of the public sense of justice. Some of the examples are the verdict in the case of the environmental lawsuits of Lapindo Brantas Mud in Sidoarjo, the case verdict in Palembang District Court on the lawsuit filed by the Ministry of Environment and Forestry on forest fires and land concessions of PT. Bumi Mekar Hijau in 2014. From the decisions, it turned out that the judges, in making the legal arguments for their decisions, had deviated from the analogy and were not based on the existing legal facts. In building legal arguments, it would have to be conducted by collecting data (evidence) and clear fact so that its solutions do not deviate from the rules of law